Pelatihan Disinfeksi Lingkungan Bagi Masyarakat Untuk Penanggulangan dan Pencegahan Penularan COVID-19: Pelatihan Disinfeksi Lingkungan Bagi Masyarakat Untuk Penanggulangan dan Pencegahan Penularan COVID-19 - Cok Dewi Widhya Hana Sundari; I Gusti Ayu Sri Dhyanaputri; Nur Habibah; Heri Setiyo Bekti (Yayasan Ahmad Mansyur Nasirah, 2022)
Since its emergence at the end of 2019, WHO has designated COVID-19 as a pandemic after 114 countries were infected by the virus. The rate of transmission and spread of this virus is very massive. COVID-19 can be transmitted easily from human to human through close contact and droplets. According to several studies, the corona virus that sticks to various surfaces of objects can be effectively removed by using various types of disinfectants. The widespread use of disinfectant liquids in the community is not accompanied by sufficient knowledge, causing misuse which causes less effective disinfection and can even cause side effects for health and negative impacts on the environment. The purpose of this activity is to provide education to the public so that they understand how to manufacture and use disinfectants properly so that they are effective and avoid side effects on health. Implementation of this activity were 60 people, consisting of: representatives from the village apparatus, Sekehe Teruna Teruni, PKK and health cadres representing the Cempaga village, Bangli distric-Province of Bali. The method of devotion carried out in this activity are the lecture, discussion and training method. The training was held for 3 (three) days, consisting of lectures on disinfectants and environmental disinfection methods, as well as demonstrations of making disinfectants delivered by village representatives. The result of this activity is that there is an increase in knowledge about COVID-19 targeted training at the level of knowledge category both before training by 25% and after training to 63.33%. And there is an increase in knowledge about environmental disinfection for the prevention of COVID-19 training targets at the level of knowledge both before training by 16.67% and after training to 63.33%. It is recommended to carry out environmental disinfection in the surrounding environment using household materials and carry out environmental disinfection safely both for public health and for the surrounding environment.